2019
DOI: 10.5213/inj.1938032.016
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Urinary Sphincter Cuff Size Predicts Outcome in Male Patients Treated for Stress Incontinence: Results of a Large Central European Multicenter Cohort Study

Abstract: PurposeThe aim was to study the correlation between cuff size and outcome after implantation of an AMS 800 artificial urinary sphincter.MethodsA total of 473 male patients with an AMS 800 sphincter implanted between 2012 and 2014 were analyzed in a retrospective multicenter cohort study performed as part of the Central European Debates on Male Incontinence (DOMINO) Project.ResultsSingle cuffs were implanted in 54.5% and double cuffs in 45.5% of the patients. The cuffs used had a median circumference of 4.5 cm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…As expected, AUS survival rates decreased over time. We found AUS survival rate of 17% at 14 years, and similar findings have been reported by Boswell et al 20 One possible explanation for differences in previously reported explantation rates could be due to the follow‐up time The global explanation rate has been shown in several studies as 21.1% 21 and 29.1%, 22 and in our study, 23.2% had AUS removal. In a study reported in 2020, the surgical procedures and outcomes were retrospectively analyzed in a total of 473 patients who received AMS 800, and showed better continence results and lower revision rates at high‐volume centers 23 .…”
Section: Discussionsupporting
confidence: 90%
“…As expected, AUS survival rates decreased over time. We found AUS survival rate of 17% at 14 years, and similar findings have been reported by Boswell et al 20 One possible explanation for differences in previously reported explantation rates could be due to the follow‐up time The global explanation rate has been shown in several studies as 21.1% 21 and 29.1%, 22 and in our study, 23.2% had AUS removal. In a study reported in 2020, the surgical procedures and outcomes were retrospectively analyzed in a total of 473 patients who received AMS 800, and showed better continence results and lower revision rates at high‐volume centers 23 .…”
Section: Discussionsupporting
confidence: 90%
“…Thereby, this is true for both studies showing the lowest stricture rates in case of AUS erosion. The impact of AUS cuff size on outcomes and complication rates is still discussed ( 25 ), though most authors did not report increased adverse results for the implantation of smaller AUS cuff sizes ( 26 , 27 ). Regarding urethral erosions, our findings together with Agarwal et al might point to a possible influence on urethral erosions and following risk of urethral stricture formation, which needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Utomo et al already detected unspecified tissue damage requiring revision during a short followup in 3.7 % of patients who received the adjustable balloon device ProAct (9). Urethral erosion after AUS implantation is also attributed to urethral atrophy caused by circular compression and impaired perfusion (12,13). Apart from the risk of urethral erosion, urethral atrophy in the cuff area also harbors the risk of recurrent incontinence through inadequate urethral closure.…”
Section: Discussionmentioning
confidence: 99%